2021
DOI: 10.1002/jsfa.11354
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of gibberellin A3, glycine betaine, and Si, Ca, and K fertilizers on physiological disorders and yield of pomegranate cv. Wonderful

Abstract: BACKGROUND: Damage from cracking, russeting, and sunscalds causes significant yield losses in pomegranate worldwide and may result from stressful environmental conditions. Although foliar sprays with minerals or growth regulators could be an important orchard management, little is known on the effectiveness of glycine betaine, silicon (Si)-based fertilizers or the response of cv. Wonderful to gibberellin A 3 (GA 3 ). RESULTS: During a 2-year study, foliar spraying with GA 3 at 75 or 150 mg L −1 applied in July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…tZOG is one of the plant cytokinins, which is beneficial to improve the proliferation capacity of plant cells, as well as to improve the photosynthetic capacity of plants [ 47 ]. GA 3 can enhance plant resistance to external environmental stress, reduce ABA content in plants, promote plant growth, and increase plant yield [ 48 , 49 ]. The level of abscisic acid is a response of plants to adversity stress, and under long-term adversity stress, ABA accumulation in plants increase, plant resistance decrease, and plants gradually age [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…tZOG is one of the plant cytokinins, which is beneficial to improve the proliferation capacity of plant cells, as well as to improve the photosynthetic capacity of plants [ 47 ]. GA 3 can enhance plant resistance to external environmental stress, reduce ABA content in plants, promote plant growth, and increase plant yield [ 48 , 49 ]. The level of abscisic acid is a response of plants to adversity stress, and under long-term adversity stress, ABA accumulation in plants increase, plant resistance decrease, and plants gradually age [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In shaping plant morphological characteristics and enhancing population photosynthesis, Gong et al (2021) revealed that EDAH (1.5 mL L -1 )+DA-6 (1 mL L -1 ) treatment in a certain concentration could improve the yield of summer maize (Zea mays L.) Ali et al (2022) sprayed the 24epibrassinolide (EBL) solution in a certain concentration on strawberry (Fragaria ×ananassa Duchesne ex Rozier) plants, finding that EBL treatment could not only improve the vegetative growth of such fruits but also improve the yield and quality. Spraying plant growth regulators on Punica granatum (Drogoudi and Pantelidis, 2022), Prunus (Time et al, 2021), Vitis (Li et al, 2022), Prunus armeniaca (Roussos et al, 2021) and other commercial crops has also been found to significantly improve fruit yield and quality. Hence, the application of plant growth regulators has emerged as a significant method for improving fruit quality.…”
Section: Introductionmentioning
confidence: 99%